2019
DOI: 10.1302/1863-2548.13.180156
|View full text |Cite
|
Sign up to set email alerts
|

Functional outcome of the elbow in toddlers with transphyseal fracture of the distal humerus treated surgically

Abstract: Purpose To quantitatively evaluate the upper extremity and elbow function with the Mayo Elbow Performance Score (MEPS) in children with transphyseal fracture of the distal humerus (TFDH) treated surgically. Methods During the period between 2005 and 2015, a total of 16 patients (ten male, six female) met the inclusion criteria. Mean age at the time of injury was 18 months (11 to 37) and mean follow-up was 42.3 months (6 to 98). Based on a modified version of Delee’s classification (Group A to C), the clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 34 publications
0
27
0
1
Order By: Relevance
“…In addition to the varus on the coronal plane, the cubitus varus can also include the three-plane deformities of the overextension on the sagittal plane and the internal rotation on the horizontal plane [4]. Besides, due to the poor ability of distal humeral epiphysis to correct the existed varus deformity, the cubitus varus deformity will persist into adulthood without any improvement [5, 6]. Thus, the cubitus varus deformity will not only affect the esthetic appearance and restrict the elbow motion, but also delay the daily life and learning of adolescents to a certain extent [7].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the varus on the coronal plane, the cubitus varus can also include the three-plane deformities of the overextension on the sagittal plane and the internal rotation on the horizontal plane [4]. Besides, due to the poor ability of distal humeral epiphysis to correct the existed varus deformity, the cubitus varus deformity will persist into adulthood without any improvement [5, 6]. Thus, the cubitus varus deformity will not only affect the esthetic appearance and restrict the elbow motion, but also delay the daily life and learning of adolescents to a certain extent [7].…”
Section: Introductionmentioning
confidence: 99%
“…Secondly, owing to the less remodeling potential of the distal humerus, the cubitus varus seem to be not progressive [27] . an the inadequate reduction could be the main cause of cubitus varus in toddlers with TFDH 6 . In present study, all the reduction was guided by the US, and nearly anatomy reduction could be guaranteed in most cases which thus avoiding the cubitus varus effectively.…”
Section: Discussionmentioning
confidence: 98%
“…Owing to the low incidence of TFDH, many previous studies just reported case reports on this injury with limited impacts on the treatment of TFDH. Recently, some studies reported retrospective studies with small number of consecutive cases [5,6] . However, the consensus on the normalized treatment has not been reached, and it is still a need of further seeking on the most appropriate treatment strategy for the TFDH.…”
Section: Introductionmentioning
confidence: 99%
“…Many authors recommend avoiding late manipulation after 4-7 days) owing to concerns about avascular necrosis, trauma to the growth plate, and disturbance of growth [11]. Some authors prefer intraoperative arthrography for these patients because of the diffi culty in visualizing the distal humeral anatomy in very young children [1,4], for obtaining good alignment of fracture and stability in such cases [12].…”
Section: Case Reportmentioning
confidence: 99%
“…Transepiphyseal Fracture of Distal Humerus ( TFDH ) or epiphysiolysis of distal humerus is a rare injury seen in children younger than three years of age [1]. It is the least commonest of all physeal injuries representing 3.9% of them in this age group [2].…”
Section: Introductionmentioning
confidence: 99%